2014
DOI: 10.1186/1472-6882-14-283
|View full text |Cite
|
Sign up to set email alerts
|

Equisetum arvense (common horsetail) modulates the function of inflammatory immunocompetent cells

Abstract: BackgroundIn Europe, extracts of Equisetum arvense (common horsetail) have a long tradition in the treatment of inflammatory disorders. To understand the molecular basis for its use, we investigated the immunomodulatory capacity of a standardized commercially available common horsetail extract on human primary lymphocyte function in vitro.MethodsThe standardized extract of Equisetum arvense was phytochemically characterized. Effects on proliferation, viability and activity of mitogen-activated human lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…In addition, this study examined if soluble silica has anti-inflammatory properties by analyzing several parameters that are crucial for the activation and function of lymphocytes. Results are in line with our previous study [17] and further demonstrate that suppression of human immune cell function by horsetail preparations, pictured by an inhibition of proliferation and activation of human lymphocytes via an IL-2-dependent mechanism, is dependent on the silica concentration of the horsetail preparation. Although an increase in the number of apoptotic cells was measurable at high concentrations, retardation of T cell proliferation was not solely based on apoptosis induction since effects were still measurable at lower concentrations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, this study examined if soluble silica has anti-inflammatory properties by analyzing several parameters that are crucial for the activation and function of lymphocytes. Results are in line with our previous study [17] and further demonstrate that suppression of human immune cell function by horsetail preparations, pictured by an inhibition of proliferation and activation of human lymphocytes via an IL-2-dependent mechanism, is dependent on the silica concentration of the horsetail preparation. Although an increase in the number of apoptotic cells was measurable at high concentrations, retardation of T cell proliferation was not solely based on apoptosis induction since effects were still measurable at lower concentrations.…”
Section: Discussionsupporting
confidence: 92%
“…Therein, fields of internal application are defined for inflammatory diseases of the urinary tract and external application for the treatment of poorly healing wounds. The additional putative medicinal properties are supported by a variety of studies that found diuretic [6], antibacterial [7][8][9], and antioxidant effects [10][11][12][13][14] as well as immunomodulatory properties for the treatment of immune dysfunctions [15][16][17]. We assumed that the medicinal properties of horsetail are at least partly mediated by the high silica content, as it can amount to up to 25 % of the dry weight of the plant [3].…”
Section: CDmentioning
confidence: 98%
“…Equisetum arvense , native to the Arctic and temperate regions of Europe, belongs to the Equisetopsida family, and it is commonly used as a herbal remedy. The phytotherapic properties are anti‐bacterial (Bessa Pereira et al., ; Milovanović, Radulović, Todorović, Stanković, & Stojanović, ), antioxidant (Cetojević‐Simin et al., ; Wu et al., ) and anti‐inflammatory (Gründemann et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The activation state of T lymphocytes was determined via cellsurface analysis of CD25 and CD69, as previously reported (Gründemann et al, 2014). Briefly, cells were treated for 24 h. Then, cells were washed with PBS and stained with PE-labeled, anti-CD25 mAbs; FITC-labeled, anti-CD69; and, for the differentiation of CD4 + and CD4 -T cells, with APC-labeled, anti-CD4 mAbs (all from eBioscience, Frankfurt, Germany) for 20 min at 4°C.…”
Section: Analysis Of Activation Marker Of T Cellsmentioning
confidence: 99%